2018
DOI: 10.1371/journal.pone.0194750
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate dynamics during cardio-pulmonary exercise testing are associated with glycemic control in individuals with type 1 diabetes

Abstract: IntroductionThis study investigated the degree and direction (kHR) of the heart rate to performance curve (HRPC) during cardio-pulmonary exercise (CPX) testing and explored the relationship with diabetes markers, anthropometry and exercise physiological markers in type 1 diabetes (T1DM).Material and methodsSixty-four people with T1DM (13 females; age: 34 ± 8 years; HbA1c: 7.8 ± 1% (62 ± 13 mmol.mol-1) performed a CPX test until maximum exhaustion. kHR was calculated by a second-degree polynomial representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…The most plausible and actually valid explanation for the different HRPC patterns was found for β1-receptor sensitivity shown by our study group (9). This hypothesis was supported most recently by results from cardio-pulmonary exercise testing in individuals with type 1 diabetes (10) where the degree of HRPC deflection was significantly lower in individuals with type 1 diabetes compared to matched controls. These authors concluded, that constantly elevated HbA 1c levels and concomitantly elevated catecholamine levels and/or inflammation induced chronic stress impairs β1-receptor sensitivity, which alters the degree and direction of the HRPC.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The most plausible and actually valid explanation for the different HRPC patterns was found for β1-receptor sensitivity shown by our study group (9). This hypothesis was supported most recently by results from cardio-pulmonary exercise testing in individuals with type 1 diabetes (10) where the degree of HRPC deflection was significantly lower in individuals with type 1 diabetes compared to matched controls. These authors concluded, that constantly elevated HbA 1c levels and concomitantly elevated catecholamine levels and/or inflammation induced chronic stress impairs β1-receptor sensitivity, which alters the degree and direction of the HRPC.…”
Section: Introductionsupporting
confidence: 86%
“…Also aerobic exercise training was shown to reduce circulating catecholamine's (33), which counteracts reduced β-adrenergic density due to overactivation of the sympathetic nervous system and concomitant chronic catecholamine stimulation (34). Thus, sensitization of the β1-receptor through regular exercise might normalize atypical HRPC provoked by chronic stress due to diseases such as type 1 diabetes (10) or cardiovascular disease (11) as shown recently (7).…”
Section: Performance Differencesmentioning
confidence: 88%
“…Additionally, the heart rate turn point was defined as the point of intersection of two regression lines in the heart rate to performance curve between LTP 1 and the maximum power output with minimal standard deviation of the two straight lines. The degree and direction of the deflection of the heart rate to performance curve (k HR ) was calculated by a second-degree polynomial function between LTP 1 and the maximum power output ( 12 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…As shown previously, different threshold concepts are suitable for healthy ( 6 , 19 ) and T1D individuals ( 20 , 21 ). The first threshold occurring during cardio-pulmonary exercise (CPX) testing [e.g., first lactate turn point (LTP 1 ) or the first ventilatory threshold (VT 1 )] translates to the inability of the muscle to entirely oxidize produced lactate and therefore it is partly shifted into the blood stream and can be metabolized by other organs.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, the HRPC of patients who survived a myocardial infarction is frequently characterized by an upward deflection, and individuals with a more pronounced upward deflection show a more pronounced reduction of LVEF . The pathophysiological value of the HRPC deflection is also supported by more atypical forms in type I diabetic patients with higher HbA1c values …”
Section: Introductionmentioning
confidence: 95%